CONCEPTUAL PRINCIPLES OF COMPETITIVE POSITIONING OF DOMESTIC AGRICULTURAL BUSINESS ON THE GLOBAL MARKET - Baula, O. V. (The actual problems of regional economy development, 2024)
The purpose of the article is to solve the scientific task of identifying the features of the European innovation and investment model of agrarian policy; consideration of the stages of the European agricultural policy; highlighting factors of the potential of the agricultural sector of Ukraine regarding its positioning on the world market; outline the vectors of the updated strategy for the development of agrarian business in Ukraine based on the European innovation and investment model. The methodological basis of the research is a set of methods of general scientific knowledge. The method of historical-logical knowledge - when considering the stages of European agrarian policy; the method of analysis and synthesis - when identifying the features of the European innovation and investment model of agrarian policy; method of systematization and generalization - when identifying factors of the potential of the agricultural sector of Ukraine regarding its positioning on the world market; empirical methods of scientific knowledge - to outline the vectors of the updated strategy for the development of agrarian business in Ukraine based on the European innovation and investment model. It has been found that it is advisable to consider the market of agro-food products as an economic system that is subject to regulation in several aspects: as an institutional and organizational unity of producers, consumers and infrastructure; as a set of relations where the state plays a regulatory role between its constituents; as an economic and social institution, which is characterized by the cyclicality of all stages of agricultural production, including the distribution, exchange and consumption of agricultural products. It is proven that the positioning of the country on the world market directly depends on the situation at the national level (productivity and qualification of personnel, production process technologies, investments, infrastructure development, use of scientific and technical achievements, etc.). In order to achieve the goals outlined in the National Economic Strategy for the period until 2030 regarding the formation of a competitive agricultural sector of Ukraine, it is advisable to use the experience of the EU SAP. However, using the potential of European integration requires significant efforts to transform the agro-industrial sector based on the innovation-investment model. It is substantiated that the main goal of the regulatory agrarian policy should be to ensure the proper balancing of the interests of all participants in market agreements. Practically, this balancing is achieved mainly with the help of two main components: regulation of the market of agro-food products and development of rural areas, which involves provision of appropriate institutional infrastructure. It is argued that it is expedient to base the updated strategy of agricultural business development in Ukraine on the European innovation and investment model. The results of the study can be useful for the development of scientifically based recommendations for the implementation of the innovation-investment model in agrarian policy.